2001
DOI: 10.1161/01.atv.21.4.548
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-Mediated Transfer of Dominant-Negative Rho-Kinase Induces a Regression of Coronary Arteriosclerosis in Pigs In Vivo

Abstract: Abstract-Small GTPase Rho and its target Rho-kinase/ROK/ROCK play an important role in various cellular functions, including smooth muscle contraction, actin cytoskeleton organization, and cell adhesion and migration, all of which may be involved in the pathogenesis of arteriosclerosis. Here, we show that adenovirus-mediated transfer of dominantnegative Rho-kinase (DNRhoK) induces a marked regression of coronary constrictive remodeling and abolishes coronary vasospastic activity in vivo. Porcine coronary segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 46 publications
1
55
1
Order By: Relevance
“…We used the extent of ERM phosphorylation as a marker of Rho-kinase activity. [42][43][44] Determination of Akt Binding to eNOS. Akt was immunoprecipitated from liver tissue lysates (800 mg) using 5 mL rabbit polyclonal anti-Akt antibody conjugated with protein G-Sepharose (30 mL; GE Healthcare, Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…We used the extent of ERM phosphorylation as a marker of Rho-kinase activity. [42][43][44] Determination of Akt Binding to eNOS. Akt was immunoprecipitated from liver tissue lysates (800 mg) using 5 mL rabbit polyclonal anti-Akt antibody conjugated with protein G-Sepharose (30 mL; GE Healthcare, Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…13 Bovine pulmonary endothelial cells were infected at 80% confluence with the indicated recombinant adenoviruses (Ad-LacZ or Ad-DN-Rho-kinase) at a multiplicity of infection of 200. Approximately 24 hours later, cells were either exposed to normoxia (20% O 2 ) or hypoxia (3% O 2 ) for 24 hours before…”
Section: Overexpression Of Dominant-negative Rho-kinasementioning
confidence: 99%
“…The rabbit polyclonal antibody recognized Thr(558) phosphorylation of ezrin and radixin and Thr(564) phosphorylation of moesin. 13 The specificity of the Rho-kinase antibody has been described. 14 The antibody detection kit (enhanced chemiluminescence) and the nylon and polyvinylidene difluoride transfer membranes were purchased from Amersham Corp.…”
mentioning
confidence: 99%
“…To evaluate the intracellular enzymatic sources responsible for the I/R-induced production of ROS, the measurement was also performed in the presence of the following drugs: (1) indomethacin (100 mM, cyclooxygenase inhibitor), 44 (2) rotenone (5 mM, mitochondrial complex I inhibitor) 45 and (3) apocynin (100 and 200 mM, NADPH oxidase inhibitor). 23,46 Adenovirus-mediated in vivo gene transfer of dominant-negative Rho-kinase into hepatocyte Adenovirus vectors with a mutant (NK1036-TT) Rhobinding (RB) domain of Rho-kinase with a pleckstrin homology domain [RB/PH (TT)] (AdDNRhoK[RB/ PH(TT)]), 20 which are DNRhoK mutants driven by the cytomegalovirus promoter with a c-myc tag, were prepared through homologous recombination between co-transfected pJM17 and the shuttle plasmid in 293 cells. Integration of the transgene into the adenoviral genome was determined by a polymerase chain reaction and restriction analysis.…”
Section: Measurement Of Superoxide Production In Liver Tissuementioning
confidence: 99%
“…17 We have demonstrated that Rho-kinase is substantially involved in the pathogenesis of cardiovascular diseases in both animals and humans. [18][19][20][21] Rho-kinase is also known to regulate the mechanism of ROS production. 17,22,23 Indeed, we have also recently demonstrated that Rhokinase is involved in the ROS production in the hyperacute phase of the reperfusion and pro-inflammatory cytokine production in hepatic I/R injury in rats in vivo.…”
Section: Introductionmentioning
confidence: 99%